EFFECT OF RUDDER DESIGN ON HYDRODYNAMIC FORCES OF AUTONOMOUS UNDERWATER GLIDER - ZAKARIA, MOHAMAD SYAMIM (IRC, 2017)
An autonomous underwater glider (AUG) is a vehicle with fixed-wing. They move through the ocean by changing the buoyancy to follow a “Saw-tooth” pattern of motion. In this project, a part of AUGs which is rudder design is studied. Specifically, the relationship between rudder design and lift and drag of hydrodynamic forces is investigated. The comparative study is done between conventional rudder and schilling/ fishtail rudder. For the modelling works, SOLIDWORKS is used to create the model. ANSYS code "Fluent” is used to do analysis on hydrodynamic performance such as lift force of AUGs. The numerical simulation is done at various angle of attack from 0°- 20°. The result from the simulation shown that the fishtail rudder has higher lift coefficients and can produce better maneuvering performance compare to conventional rudder.